PENGARUH MOTIVASI, CITRA LEMBAGA, KELUARGA, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN KONSUMEN DALAM PEMILIHAN JASA KURSUS - Aegis Dhimas Erlangga, Sunarso & Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study was to analyze the significance of the effect ofmotivation, the image of the institution, families and groups of reference to consumerdecisions. This study is a survey. The study population is students LPK FujiyamaGakkoo in Surakarta totaling 120 people. The research sample of 60 people with simplerandom sampling technique. Data collection technique used questionnaire, observationand documentation. Data were analyzed used multiple linear regression, t-test, F andcoefficient of determination. The results showed motivation has significant effect onconsumer decisions in the selection of service courses on Fujiyama LPK Gakko inSurakarta. The image of the institutions has significant effect on consumer decisions inthe selection of service courses on Fujiyama LPK Gakko in Surakarta. Families has asignificant effect on consumer decisions in the selection of service courses on FujiyamaLPK Gakko in Surakarta. Reference group has a significant effect on consumer decisionsin the selection of service courses on Fujiyama LPK Gakko in Surakarta.Keywords: motivation, image of institution, families, group of references